2016
DOI: 10.1002/iub.1519
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic investigations of DKK‐1 and PDCD5 expression levels as independent prognostic markers of human chondrosarcoma

Abstract: In this study, we investigated the expression levels of Dickkopf-1 (DKK-1) and programmed cell death 5 (PDCD5) by using quantitative real-time PCR and immunohistochemistry in patients with chondrosarcoma. The DKK-1 mRNA levels were significantly higher in chondrosarcoma when compared with the corresponding nontumor tissues (mean 6 SD: 4.23 6 1.54; 1.54 6 0.87; P 5 0.001). PDCD5 mRNA levels were remarkably deceased in tumor tissues when compared with corresponding nontumor tissues (mean 6 SD: 1.94 6 0.73; 5.42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We hypothesize that this inactivation could be explained, at least in part, by the high levels of several Wnt antagonists, such as DKK-1, DKK-3 and/or DKK-4. DKK-1 in particular has been found to be overexpressed in a plethora of tumors with a clear oncogenic function [ 17 , 18 , 19 ]. In this context, it has been demonstrated that the reactivation of the Wnt/β-catenin pathway by Glycogen synthase kinase 3 inhibitors has anti-oncogenic effects in RMS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this inactivation could be explained, at least in part, by the high levels of several Wnt antagonists, such as DKK-1, DKK-3 and/or DKK-4. DKK-1 in particular has been found to be overexpressed in a plethora of tumors with a clear oncogenic function [ 17 , 18 , 19 ]. In this context, it has been demonstrated that the reactivation of the Wnt/β-catenin pathway by Glycogen synthase kinase 3 inhibitors has anti-oncogenic effects in RMS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many tumors, DKK-1 clearly acts only as an oncogene ( Supplementary Table S1 ). For instance, several studies showed a relationship between DKK-1 overexpression and worse prognosis in common tumors such as lung cancer (including non-small cell lung cancer) [ 27 , 28 ] and rare malignancies such as chondrosarcoma [ 29 , 30 ]. However, the setting is highly complex and a clear oncogenic or anti-oncogenic role of DKK-1 in a given tumor type is not always clear, with a plethora of examples in which references to both sides may be found.…”
Section: The Dickkopf (Dkk) Family and Its Role In Cancermentioning
confidence: 99%
“…indicated the upregulation of Oct‐4 was upregulated in metaplastic pancreatic ducts compared with normal acini and pancreatic carcinoma. Furthermore, many markers for early diagnosis of the various cancers earlier have conducted . Therefore, this study was aimed to investigate the clinical significance of MUC5AC and Oct‐4 expression in patients with GC in an Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many markers for early diagnosis of the various cancers earlier have conducted. [15][16][17] Therefore, this study was aimed to investigate the clinical significance of MUC5AC and Oct-4 expression in patients with GC in an Iranian population.…”
Section: Introductionmentioning
confidence: 99%